Total Lagrangian Material Point Method simulation of the scratching of high purity coppers. (15th March 2022) - de Vaucorbeil, Alban; Nguyen, Vinh Phu; Hutchinson, Christopher R.; Barnett, Matthew R.
Abstract: In many industries, e.g., mining and agricultural industry, minerals handling, wear in machine elements causes functional surfaces to degrade, eventually leading to material failure or loss of functionality. To understand the abrasive wear resistance of materials scratch tests are sometimes conducted. However, the amount of information that can be obtained from well-defined scratch tests is limited due to the coupling of different physical processes, with a complex stress state. This paper presents a study of the Total Lagrangian Material Point Method (TLMPM) for the simulation of scratch tests. To this end we simulate the scratch of high purity coppers and compare with existing smooth particle hydrodynamics results and experiments. The results show that the TLMPM is stable for any indentation loads considered in the experiments and the results are in excellent agreement with experiments when friction is considered. Moreover, the results show the presence of oscillations in the groove profile at high loads, with and without friction. We show that the origin of these oscillations is linked to both the plastic strain and work hardening rates. Highlights: The Total Lagrangian Material Point Method is suited to the simulation of scratch tests. The TLMPM performed better than SPH for the simulation scratch tests in high purity copper. When friction is considered, TLMPM scratch tests simulations are in very good agreement with experiments. The origin of oscillations appearing in the forces and groove profiles are discussed: they depend on both the plastic strain and work hardening rates.